2021
DOI: 10.1155/2021/6629758
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Heterogeneity Characteristics of Geological Controls on Coalbed Methane Accumulation in Gujiao Coalbed Methane Field, Xishan Coalfield, China

Abstract: Commercial exploration and exploitation of coalbed methane (CBM) in Gujiao coalbed methane (CBM) field, Xishan coalfield, have rapidly increased in recent decades. The Gujiao CBM field has shown strong gas distribution heterogeneity, low gas content, and wide distribution of wells with low production. To better understand the geological controlling mechanism on gas distribution heterogeneity, the coal reservoir evolution history and CBM accumulation process have been studied on the base of numerical simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…During the evaluation of favorable area for CBM development, the selection of main controlling factors must follow the principle of ‘selecting the main geological parameters, and each parameter is independent of others’. 37 Geological parameters utilized in the evaluation of favorable areas for CBM development include direct parameters (e.g., gas content, permeability, burial depth, reservoir pressure, critical desorption pressure, etc.) and indirect parameters (e.g., hydrogeological condition, crustal stress, and tectonic characteristics, etc.…”
Section: Evaluation Methods Of Favorable Area Based On Vwmmentioning
confidence: 99%
See 3 more Smart Citations
“…During the evaluation of favorable area for CBM development, the selection of main controlling factors must follow the principle of ‘selecting the main geological parameters, and each parameter is independent of others’. 37 Geological parameters utilized in the evaluation of favorable areas for CBM development include direct parameters (e.g., gas content, permeability, burial depth, reservoir pressure, critical desorption pressure, etc.) and indirect parameters (e.g., hydrogeological condition, crustal stress, and tectonic characteristics, etc.…”
Section: Evaluation Methods Of Favorable Area Based On Vwmmentioning
confidence: 99%
“…Based on the production conditions and the degree of geological exploration in the study area, combined with the results of our previous research, 37 the following nine factors were selected as the main controlling factors ( Table 1 ).…”
Section: Evaluation Methods Of Favorable Area Based On Vwmmentioning
confidence: 99%
See 2 more Smart Citations
“…CBM resources are abundant in the Gujiao mining area, but the reservoir pressure, gas content, groundwater flow field and other parameters have obvious spatial distribution heterogeneity (Yan et al, 2021;Li et al, 2021). It is reported that the tectonic type, roof lithology, burial depth and groundwater dynamic conditions have significant effects on the reservoir .…”
Section: Field Applicationmentioning
confidence: 99%